Correlation of anterior cerebral artery resistive index with early comorbidities in preterm neonates - Gill, Karambir Singh; Gupta, Bhavna; Pooni, Puneet A.; Bhargava, Siddharth (Frontiers in Pediatrics, 2024)
Introduction This study was undertaken to find the clinical correlation of resistive index (RI) in the anterior cerebral artery (ACA) of preterm neonates admitted to the Neonatal Intensive care unit (NICU) with comorbidities such as perinatal asphyxia, neonatal sepsis, and necrotizing enterocolitis (NEC). Methods An observational analytical study was conducted, including preterm neonates (<35 weeks) admitted to the NICU. Ultrasound cranium scans were performed on days 1–3 and 7 of life as per the study protocol. Baseline and clinical data of asphyxia, sepsis, and NEC were obtained. Images were acquired using a 4–8-MHz probe on a Sonosite M-turbo machine (Bothell, WA, USA). All statistical calculations were done using SPSS version 21.0 (SPSS Inc., Chicago, IL, USA) with the application of the Kolmogorov–Smirnov test and the Mann–Whitney test. Results During the study period, a total of 739 neonates were admitted. Of these, 73 neonates constituted the study group. Among the 73 patients, 33 were preterm neonates without comorbidities and 40 neonates had comorbidities such as perinatal asphyxia, sepsis, and NEC stage 2 and 3 (necrotizing enterocolitis). In the present study, the mean RI on day 3 of life was 0.76 ± 0.04 in neonates without comorbidities and 0.77 ± 0.04 in neonates with comorbidities, with a p-value of 0.247. On the 7th day of life, the mean RI was 0.82 ± 0.03 in both groups, with a p-value of 0.42. Conclusion We could not find any significant clinical correlation of RI in the ACA of preterm neonates <35 weeks of gestation with comorbidities.